Association of systemic medication use with Glaucoma and intraocular pressure: the European Eye Epidemiology Consortium - Vergroesen, Joëlle; Schuster, Alexander K.; Stuart, Kelsey V.; Asefa, Nigus G.; Cougnard-Grégoire, Audrey; Delcourt, Cécile; Schweitzer, Cédric; Barreto, Patrícia; Coimbra, Rita; Foster, Paul J.; Luben, Robert N.; Pfeiffer, Norbert; et al. (Ophthalmology, 2023)
Purpose - To investigate the association of commonly used systemic medications with glaucoma and intraocular pressure (IOP) in the European population. - Design - Meta-analysis of 11 population-based cohort studies of the European Eye Epidemiology Consortium. - Participants - The glaucoma analyses included 143 240 participants and the IOP analyses included 47 177 participants. - Methods - We examined associations of 4 categories of systemic medications—antihypertensive medications (β-blockers, diuretics, calcium channel blockers [CCBs], α-agonists, angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers), lipid-lowering medications, antidepressants, and antidiabetic medications—with glaucoma prevalence and IOP. Glaucoma ascertainment and IOP measurement method were according to individual study protocols. Results of multivariable regression analyses of each study were pooled using random effects meta-analyses. Associations with antidiabetic medications were examined in participants with diabetes only. - Main Outcome Measures - Glaucoma prevalence and IOP. - Results - In the meta-analyses of our maximally adjusted multivariable models, use of CCBs was associated with a higher prevalence of glaucoma (odds ratio [OR], 1.23; 95% confidence interval [CI], 1.08 to 1.39). This association was stronger for monotherapy of CCBs with direct cardiac effects (OR, 1.96; 95% CI, 1.23 to 3.12). No other antihypertensive medications, lipid-lowering medications, antidepressants, or antidiabetic medications were associated with glaucoma. Use of systemic β-blockers was associated with a lower IOP (β coefficient, −0.33 mmHg; 95% CI, −0.57 to −0.08 mmHg). Monotherapy of both selective systemic β-blockers (β coefficient, −0.45 mmHg; 95% CI −0.74 to −0.16 mmHg) and nonselective systemic β-blockers (β coefficient, −0.54 mmHg; 95% CI, −0.94 to −0.15 mmHg) was associated with lower IOP. A suggestive association was found between use of high-ceiling diuretics and lower IOP (β coefficient, −0.30 mmHg; 95% CI, −0.47 to −0.14 mmHg) but not when used as monotherapy. No other antihypertensive medications, lipid-lowering medications, antidepressants, or antidiabetic medications were associated with IOP. - Conclusions - We identified a potentially harmful association between use of CCBs and glaucoma prevalence. Additionally, we observed and quantified the association of lower IOP with systemic β-blocker use. Both findings potentially are important, given that patients with glaucoma frequently use systemic antihypertensive medications. Determining causality of the CCB association should be a research priority. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.